Adrenal tumours: 10-year experience of a tertiary cancer centre - Shanmugam, Subbiah; Susikar, Sujay; Raja, Gerald Anand; Reddy, Kishore Kumar (International Surgery Journal, 2021)
Adrenal tumours are rare neoplasm. The prevalence of adrenal tumours is estimated to be 3% in those older than 50 years and 6% in those older than 60 years. Diagnostic work-up should assess autonomous hormone production and differentiate between benign and malignant lesions. In 19 patients presenting with adrenal tumours from 2010-2020, 9 (47.4%) were male patients and 10 (52.6%) female patients with a mean age of 44.6 years. Presenting complaints include headache and hypertension in 8 (42.1%) patients, pain abdomen in 4 (21.1%) patients, incidentally diagnosed in 5 (26.3%) patients and 2 (10.5%) patients presented with mass per abdomen. Pheochromocytoma was seen in 10 (52.6%) patients, adrenocortical carcinoma was seen in 5 (26.3%) patients, adenoma was seen in 3 (15.8%) patients each and angiomyolipoma was seen in 1 (5.3%) patient. Open adrenalectomy was done in 13 (68.4%) patients and laparoscopic adrenalectomy was done in 5 (26.3%) patients. One patient presented with multiple metastases and was inoperable. Adrenal tumours are rare neoplasms often presenting with nonspecific symptoms. The majority are non-functioning tumours with an incidence in the 5th or 6th decade. In our study pheochromocytoma is most common followed by adrenocortical carcinoma. Laparoscopic adrenalectomy is now the gold standard for small and medium-sized tumours.